2010
DOI: 10.1111/j.1755-3768.2008.01494.x
|View full text |Cite
|
Sign up to set email alerts
|

Nd:YAG laser goniopuncture after deep sclerectomy: outcomes

Abstract: ABSTRACT.Purpose: This study aimed to investigate the safety and efficacy of Nd:YAG laser goniopuncture (LGP) in lowering intraocular pressure (IOP) after deep sclerectomy (DS). Methods: We reviewed the outcomes in 258 eyes of 258 consecutive patients who underwent DS or combined phacoemulsification and DS between August 2001 and December 2003. Mitomycin C was used during surgery in 192 eyes (74.4%). Results: Mean follow-up was 40 ± 11 months after DS and 31 ± 12 months after LGP. Laser goniopuncture was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
3
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 22 publications
2
70
3
9
Order By: Relevance
“…28 Hypotony was observed in 3% of our cohort, which also compares favourably with the hypotonyrate of 7.2% reported by the aforementioned paper by Kirwan et al 25 Over a mean follow-up period of 63.5 months (in 296 eyes), we only observed three serious complications related to hypotony: two eyes required resuturing, whereas one resulted in delayed LGP is considered an important adjunct to DS in achieving low target IOPs. Reported rates vary from 36 to 67% 19,[28][29][30][31] The overall rate of LGP in our cohort was 54.4%. Patients in the phaco-DS with MMC group had a significantly greater chance of undergoing LGP (75.7%) compared with the unaugmented phaco-DS group (51.4%) at 5 years after surgery (P = 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Hypotony was observed in 3% of our cohort, which also compares favourably with the hypotonyrate of 7.2% reported by the aforementioned paper by Kirwan et al 25 Over a mean follow-up period of 63.5 months (in 296 eyes), we only observed three serious complications related to hypotony: two eyes required resuturing, whereas one resulted in delayed LGP is considered an important adjunct to DS in achieving low target IOPs. Reported rates vary from 36 to 67% 19,[28][29][30][31] The overall rate of LGP in our cohort was 54.4%. Patients in the phaco-DS with MMC group had a significantly greater chance of undergoing LGP (75.7%) compared with the unaugmented phaco-DS group (51.4%) at 5 years after surgery (P = 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed techniques for LGP and iridoplasty have already been described in a previous publication. 19 Complete (unqualified) success criteria were defined as follows: (A) IOP o19 mm Hg and/or 20% decrease from baseline off any glaucoma medications. Failure in this group was defined as IOP = 419 mm Hg or IOP not reduced by 20% of preoperative IOP or IOP o6 mm Hg on two consecutive time points after 3 months; (B) IOP o16 mm Hg and/or 30% drop from baseline off any glaucoma medications.…”
Section: Methodsmentioning
confidence: 99%
“…The techniques for LGP and iridoplasty are described in detail in a previous publication. 21 Definitions were derived from the TVT trial. 28 Reoperation for glaucoma or a complication was defined as additional surgery requiring a return to the operating theatre.…”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20] The IOP after DS can be further lowered by Nd:YAG laser goniopuncture (LGP) of the TDM. 21,22 Like with trabeculectomy, intraoperative mitomycin C (MMC) application results in lower IOPs in the long term 23,24 and bleb rejuvenation techniques like needle revision can be used. 25 DS with MMC has been reported to be a safe and effective procedure for eyes with failed trabeculectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Puncturing the trabecular Descemet membrane leads to success rates similar to those of TE. [52][53][54] Previously, Feltgen et al used an erbium(Er):YAG laser. They reported that goniopuncture in combination with cataract surgery produced an IOP reduction comparable to that of combined TE and cataract surgery.…”
Section: Goniotomymentioning
confidence: 99%